2016
DOI: 10.1177/183693911604100212
|View full text |Cite
|
Sign up to set email alerts
|

Educators' Perceptions of Facilitating Children's Participation in Early Childhood Education

Abstract: THE AIM OF THIS RESEARCH is to provide a better understanding of children's competence, vulnerability and power issues, and to promote better decision making and protection of children by educators. This means the pedagogy in early childhood education needs to be based on understanding the nature of children's participation and participatory learning. Further on it requires understanding about how the educators working in day care could aim the pedagogical process to supporting children's participation via dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In this study, children's participation is viewed through the participatory learning approach where children are seen as active agents of their learning and meaning makers of their social interactions (Kangas, Venninen & Ojala, 2016;Berthelsen, 2009). This relies strongly on the socio-cultural learning paradigm (Rogoff, 2008) in which children are viewed as active learners, agents of their lives and reproducers of the culture instead of being needy and helpless beings (Corsaro, 2011;Piaget, 1976).…”
Section: Children's Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, children's participation is viewed through the participatory learning approach where children are seen as active agents of their learning and meaning makers of their social interactions (Kangas, Venninen & Ojala, 2016;Berthelsen, 2009). This relies strongly on the socio-cultural learning paradigm (Rogoff, 2008) in which children are viewed as active learners, agents of their lives and reproducers of the culture instead of being needy and helpless beings (Corsaro, 2011;Piaget, 1976).…”
Section: Children's Participationmentioning
confidence: 99%
“…This creates a feeling of belonging where the joy of learning emerges, and motivation and resilience are developing. (Kangas, Venninen & Ojala, 2016;Kumpulainen & al., 2014).…”
Section: Children's Participationmentioning
confidence: 99%
“…Children can thus exercise influence on a range of topics from the rules that are applied in the nursery's everyday life, the daily program to the interior design of the facility. The question of which possibilities for participation children actually have in their everyday lives and how they perceive these possibilities is one which has not been sufficiently answered in the international discourse so far (for example Almqvist/Almqvist 2015, Bae 2010, Betz 2016, Harcourt/Einarsdottir 2011, Kangas et al 2016, Nentwig-Gensemann et al 2017, Quennerstedt 2015, Wood 2014).…”
Section: A New Era Of Hong Kong's Trilingual Educationmentioning
confidence: 99%
“…In different countries, national standards and curricula for preschool education emphasize the importance of child agency and the attitude towards children as competent participants in learning [10][11][12]. At the same time, we observe a shortage of participation practices that expand children's opportunities in decision-making and the substitution of participation by the "game of democracy" [1,13]. A national study of the quality of education [14] using the ECERS-R showed that in Russian preschool classrooms, children had very little time for free play and the teacher-centered pedagogy prevailed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other, "natural" (without using cultural tools) and literal understanding of preschoolers' ideas provokes the falsification of participation, selection of the most suitable ideas from the point of view of an adult, and creation of a pseudo-child environment that neither supports child initiative nor meets children's needs [1,17]. Besides, teachers who facilitate participation find it difficult to determine the boundaries and results of child participation; they do not know how to involve children into decision-making and interpret their statements [4,13].…”
Section: Introductionmentioning
confidence: 99%